SARS-CoV-2 molecular testing and whole genome sequencing following RNA recovery from used BinaxNOW COVID-19 antigen self tests - Nguyen, Phuong-Vi; Carmola, Ludy Registre; Wang, Ethan; Bassit, Leda; Rao, Anuradha; Greenleaf, Morgan; Sullivan, Julie A.; Martin, Greg S.; Lam, Wilbur A.; Waggoner, Jesse J.; Piantadosi, Anne (Journal of clinical virology, 2023)
•SARS-CoV-2 RNA from used Binax test swabs collected and stored at home can be detected by rRT-PCR and used for genotyping and full viral genome sequencing.•Used Binax test swabs provide an important opportunity to improve population-level SARS-CoV-2 genomic surveillance, as an increasing amount of testing is performed at home.•SARS-CoV-2 sequences generated from used Binax test swabs can be used to evaluate transmission clusters, identify travel-associated infections, and monitor within-patient evolution. Widespread use of over-the-counter rapid diagnostic tests for SARS-CoV-2 has led to a decrease in availability of clinical samples for viral genomic surveillance. As an alternative sample source, we evaluated RNA isolated from BinaxNOW swabs stored at ambient temperature for SARS-CoV-2 rRT-PCR and full viral genome sequencing. 81 of 103 samples (78.6%) yielded detectable RNA, and 46 of 57 samples (80.7 %) yielded complete genome sequences. Our results illustrate that SARS-CoV-2 RNA extracted from used Binax test swabs provides an important opportunity for improving SARS-CoV-2 genomic surveillance, evaluating transmission clusters, and monitoring within-patient evolution.